2007
DOI: 10.1182/blood-2006-12-063412
|View full text |Cite
|
Sign up to set email alerts
|

Potential risks of bone marrow cell transplantation into infarcted hearts

Abstract: Cellular replacement therapy has emerged as a novel strategy for the treatment of heart failure. The aim of our study was to determine the fate of injected mesenchymal stem cells (MSCs) and whole bone marrow (BM) cells in the infarcted heart. MSCs were purified from BM of transgenic mice and characterized using flow cytometry and in vitro differentiation assays. Myocardial infarctions were generated in mice and different cell populations including transgenic MSCs, unfractionated BM cells, or purified hematopoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
401
0
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 574 publications
(417 citation statements)
references
References 42 publications
7
401
0
9
Order By: Relevance
“…19 Along with the occurrence of a severe inflammatory response, the loss in ECM compliance associated with myocardium ARTICLE www.acsnano.org C remodeling has been described as one of the main limitations to resident stem/progenitor cell activation and differentiation. 28,29 The effect of increased substrate stiffness on cardiomyocyte activity has been already reported by our group and others; 14,30 thus, we hypothesized that substrate stiffening could affect …”
Section: Resultsmentioning
confidence: 69%
“…19 Along with the occurrence of a severe inflammatory response, the loss in ECM compliance associated with myocardium ARTICLE www.acsnano.org C remodeling has been described as one of the main limitations to resident stem/progenitor cell activation and differentiation. 28,29 The effect of increased substrate stiffness on cardiomyocyte activity has been already reported by our group and others; 14,30 thus, we hypothesized that substrate stiffening could affect …”
Section: Resultsmentioning
confidence: 69%
“…We do not assume that MSC transplantation actually elicited the myocardial involvement since the first patient had clearly preexisting cardiac impairment and the second patient underwent autologous and allogeneic stem cell transplantation after MSC transplantation, thereby receiving drugs of known cardiac toxicity. However, it has been reported that MSC transplantation has led to the calcification of murine myocardium (12). This is probably the result of MSC differentiation into osteoclast-like cells.…”
mentioning
confidence: 99%
“…However, matrix stiffening is more relevant for many biological events, including tissue development, wound healing and disease progression, such as fibrosis and tumour formation. For instance, fibrous scar tissue that develops after myocardial infarction is much stiffer than normal myocardium [17][18][19] , and mesenchymal stem cells (MSCs) differentiate down an osteogenic lineage and produce markers of bone when injected into infarct tissue in mice 20 . Recent evidence also suggests that matrix stiffening, which is generally regarded as an outcome of disease, may be a contributing factor in disease development.…”
mentioning
confidence: 99%